MESIN PENGERING PRODUK PERTANIAN BERTENAGA PANAS BUMI - Hasan, Achmad (Center for Environmental Technology - Agency for Assessment and Application of Technology, 2009)
Indonesia as the biggest geothermal potential country in the world. There are252 geothermal locations have been identified that distributed along a volcanicbelt extending from Sumatera, Java, Nusa Tenggara, Sulawesi, Maluku untilPapua. Utilization of this energy be side for electrical power generation, it is usedfor non electrical (direct uses) as well. In the agriculture area with high rainfall,drying process can decrease quality of crop products. The tools doesn’t produceemission and doesn’t make noises and also as clean energy. By optimization theutilization of geothermal energy that available surrounding the agriculture areacould increase the local people economic.